Physically modified bacterial cellulose biocomposites for guided tissue regeneration - de Olyveira, Gabriel Molina [UNESP]; dos Santos, Márcio Luiz [UNESP]; Riccardi, Carla dos Santos [UNESP]; Costa, Ligia Maria Manzine; Daltro, Paula Braga [UNESP]; Basmaji, Pierre; Daltro, Gildásio de Cerqueira; Guastaldi, Antônio Carlos [UNESP] (American Scientific Publishers, 2015)
Bacterial cellulose (BC) has become established as a remarkably versatile biomaterial and can be used in a wide variety of scientific applications, especially for medical devices. In this work, the bacterial cellulose fermentation process was modified by the addition of chondroitin sulfate to the culture medium before the bacteria was inoculated. Besides, the potential of gamma irradiation treatment for the modification of the BC surface properties, in enhancing its potential for biomedical applications, was also analyzed. For guided tissue regeneration purposes, biomimetic precipitation of calcium phosphate of biological interest from simulated body fluid on bacterial cellulose was studied. The influence of chondroitin sulfate on bacterial cellulose was analyzed by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM) and thermogravimetric analysis (TGA), as well as after CaP coatings produced by a biomimetic route. FTIR analysis showed interaction between bacterial cellulose nanobiocomposites and calcium phosphate. XRD demonstrated formation of amorphous calcium phosphate and sodium chloride on bacterial cellulose nanobiocomposites. SEM images proved faster calcium phosphate deposition in non-irradiated samples. The different samples showed significant variation in thermal properties.
Keywords: Bacterial cellulose; Dental materials; Nanocomposites; Nanoskin®; Scaffolds